2014
DOI: 10.1111/psq.12152
|View full text |Cite
|
Sign up to set email alerts
|

Signing Statements, Gridlock, and Presidential Strategy

Abstract: Why do presidents use signing statements? Past research has approached presidential strategy in using such statements from both policy-oriented and institutionally oriented perspectives. However, scholars have not adequately addressed the consequences of congressional ideology and gridlock on the use of presidential signing statements. This article considers congressional composition and offers two different perspectives on presidential strategy: a separation of powers perspective (i.e., presidents use signing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Consequently, the effects of ideological conflict with Congress on the exercise of presidential power, a relationship widely explored in the literature, may be conditioned on other political factors (e.g. see Kennedy, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, the effects of ideological conflict with Congress on the exercise of presidential power, a relationship widely explored in the literature, may be conditioned on other political factors (e.g. see Kennedy, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies find that divided government increases the probability that the president issues a signing statement (Berry, 2009; Kelley and Marshall, 2008, 2009, 2010), while other studies find that divided government has mixed or no effects (Kelley et al, 2013; Ostrander and Sievert, 2012; Sievert and Ostrander, 2017). Yet, some suggest that these relationships should also account for the internal fragmentation of Congress (Kennedy, 2014; Moraguez, n.d.). In addition, scholars have consistently found that presidents are more likely to issue statements on legislation that is significant and related to appropriations or foreign policy (Berry, 2009; Kelley et al, 2013; Kelley and Marshall, 2008, 2009, 2010; Ostrander and Sievert, 2012; Sievert and Ostrander, 2017).…”
Section: Introductionmentioning
confidence: 99%